Insecticide potential of two saliva components of the predatory bug Podisus nigrispinus (Heteroptera: Pentatomidae) against Spodoptera frugiperda (Lepidoptera: Noctuidae) caterpillars. (2nd January 2022) - Campos, Juliana Mendonça; Martínez, Luis Carlos; Plata-Rueda, Angelica; Weigand, Wolfgang; Zanuncio, José Cola; Serrão, José Eduardo
Abstract: The saliva of the predatory stink bug Podisus nigrispinus contains N, N -dimethylaniline (DMA) and 1, 2, 5 -trithiepane, which kill prey. The mode of action of these components remains unknown and they were evaluated in Spodoptera frugiperda caterpillars. All compounds are toxic and cause damages in the midgut cells resulting in apoptosis and necrosis. The main features of these cells are apical protrusions with nucleus released to the lumen, vesicular rough endoplasmic reticulum, autolysosomes, and electron-dense lipid droplets. The tested biogenic compounds, P. nigrispinus saliva extract, DMA, and 1, 2, 5 -trithiepane are toxic and have negative effects to S. frugiperda caterpillars.